ANALISIS PENGARUH IPM, PDRB DAN TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI INDONESIA PERIODE TAHUN 2017 – 2021 - Zikri Azriyansyah (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Poverty is a problem faced by all countries in the world, especially in developing countries. Poverty is a complex problem that is influenced by many related factors, while this study aims to analyze how and how much influence the Human Development Index, Gross Regional Domestic Product and Unemployment Rate have on Poverty Rates in Indonesia in the period 2017 to 2021. This research using multiple regression analysis with panel data as the method of analysis. This research focuses on six provinces in Indonesia as cross section data and the time range from 2017 to 2021 as time series data. The results of the study show that simultaneously there is influence between the human development index variable Gross Domestic Regional Product and the response to poverty. Then partially, the human development index variable has a negative and significant effect on the poverty variable, and for the Gross Domestic Regional Product variable it shows positive and insignificant results on the poverty variable while the relaxation variable shows positive and significant results on the poverty variable. Furthermore, the coefficient of determination shows 99.6.